1999
DOI: 10.1148/radiographics.19.2.g99mr12343
|View full text |Cite
|
Sign up to set email alerts
|

Use of Sentinel Node Lymphoscintigraphy in Malignant Melanoma

Abstract: Lymphoscintigraphy is a sensitive, inexpensive, relatively noninvasive method of identifying lymphatic drainage patterns and sentinel lymph nodes in patients with malignant melanoma. Lymphoscintigraphy with filtered technetium-99m sulfur colloid allows prompt visualization of the lymphatic system, produces high-quality images, and delivers a low radiation dose to the patient. In addition, good regional lymph node retention is seen with filtered Tc-99m sulfur colloid, improving the success rate of intraoperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…28 Various techniques and imaging agents have been developed to map lymphatic drainage from tumors, with the most common approaches being the use of blue dye with surgical dissection or injection of radiopharmaceuticals followed by evaluation with a gamma camera (ie, lymphoscintigraphy) or intraoperatively with a gamma probe. 5,6 Published reports on these approaches indicate that there is wide variation in their sensitivity for the detection of SLNs, ranging from as low as 76% to as high as 97%. [29][30][31] Furthermore, there are several limitations and potential adverse effects associated with these established lymphatic mapping techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Various techniques and imaging agents have been developed to map lymphatic drainage from tumors, with the most common approaches being the use of blue dye with surgical dissection or injection of radiopharmaceuticals followed by evaluation with a gamma camera (ie, lymphoscintigraphy) or intraoperatively with a gamma probe. 5,6 Published reports on these approaches indicate that there is wide variation in their sensitivity for the detection of SLNs, ranging from as low as 76% to as high as 97%. [29][30][31] Furthermore, there are several limitations and potential adverse effects associated with these established lymphatic mapping techniques.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11] Several radiopharmaceutical agents are used for lymphoscintigraphy, including technetium Tc 99m antinomy trisulfate colloid, Tc 99m nanocolloid, and Tc 99m sulfur colloid. 3,7 Likewise, a number of dyes have been used to localize SLNs, including methylene blue, isosulfin blue, patent blue, and fluorescein.…”
mentioning
confidence: 99%
“…However, with the technological advancements in lymphatic mapping, it has become relatively common to detect sentinel nodes in nodal basins not previous thought to receive lymphatic drainage directly from the tumor. Studies report discordance between the drainage patterns identified via lymphoscintigraphy and the predicted pattern in 32%-62% of cases of truncal melanoma (2). Therefore, removing the lymphatic basin typically containing the sentinel node does not preclude the existence of sentinel nodes in other atypical nodal basins.…”
Section: Discussionmentioning
confidence: 99%
“…In 2010, there was an estimated 68,000 new cases of melanoma and nearly 9000 melanoma-associated deaths (1). The staging, prognosis, and treatment algorithms of melanoma depend on the Breslow thickness, mitoses, and the presence or absence of regional and/or distant metastases (2). Melanoma preferentially spreads via the lymphatics, and metastases typically progress through afferent lymphatic channels to sentinel nodes before presenting in non-sentinel lymph node sites.…”
Section: Introductionmentioning
confidence: 99%
“…High falsenegative rates have generally been reported in head and neck melanomas because of the difficulties associated with the close proximity of the primary injection site and the potential SLN, but also because of the technical expertise required for successful biopsy in this area with its complex vascular and nervous structure [33,34]. Additionally, a 1-day protocol of lymphatic mapping is suggested in head and neck melanomas which should lead to a reduction of the false-negative rate [35,36]. By using a 2-day protocol, a higher number of lymph nodes identified as SLNs can be visualized, localized on distant neck levels which could be a reason for the high false-negative rate in head and neck melanomas.…”
Section: Discussionmentioning
confidence: 99%